Fitness and proteome changes accompanying the development of erythromycin resistance in a population of Escherichia coli grown in continuous culture - Petráčková, Denisa; Janeček, Jiří; Bezoušková, Silvia; Kalachová, Ladislava; Techniková, Zuzana; Buriánková, Karolína; Halada, Petr; Haladová, Kateřina; Weiser, Jaroslav (MicrobiologyOpen, 2013)
We studied the impact of a sublethal concentration of erythromycin on the fitness and proteome of a continuously cultivated population of Escherichia coli. The development of resistance to erythromycin in the population was followed over time by the gradient plate method and minimum inhibitory concentration (MIC) measurements. We measured the growth rate, standardized efficiency of synthesis of radiolabeled proteins, and translation accuracy of the system. The proteome changes were followed over time in two parallel experiments that differed in the presence or absence of erythromycin. A comparison of the proteomes at each time point (43, 68, and 103 h) revealed a group of unique proteins differing in expression. From all 35 proteins differing throughout the cultivation, only three were common to more than one time point. In the final population, a significant proportion of upregulated proteins was localized to the outer or inner cytoplasmic membranes or to the periplasmic space. In a population growing for more than 100 generations in the presence of antibiotic, erythromycin-resistant bacterial clones with improved fitness in comparison to early resistant culture predominated. This phenomenon was accompanied by distinct changes in protein expression during a stepwise, population-based development of erythromycin resistance.
Keywords: Microbial Sensitivity Tests; proteom; proteiny z Escherichia coli; erythromycin; mikrobiální testy citlivosti; Escherichia coli; antibakteriální látky; Genetic Fitness; Escherichia coli Proteins; Continuous cultivation system; Culture Media; proteome; regulace genové exprese u bakterií; časové faktory; fitness; kultivační média; Anti-Bacterial Agents; Drug Resistance, Bacterial; genetická zdatnost; Gene Expression Regulation, Bacterial; Proteome; bakteriální léková rezistence; resistance; Time Factors; Erythromycin